Odpowiedzi

Najlepsza Odpowiedź!
2010-01-26T12:23:37+01:00
Y=ax+b to jest ogolna postac rownania
A( - pier.2, -pier. 6)
B( 1, pier.3)

po podstawieniu:
- pier.6=-pier.2a +b
pier.3 = a+b => b= pier.3 -a

-pier. 2a + pier.3 - a = - pier.6
- pier.2a - a = - pier.6 - pier.3 / *(-10
pier.2a + a = pier.6 + pier.3
a(pier.2 +1)= pier.6 + pier.3
a= (pier.6+ pier.3)/(pier.2 +1)

usuwamy niewymiernosc z mianownika mnozac licznik i mianownik przez (pier.2-1)

a= (pier.6+pier.3)(pier.2-1)/(pier.2+1)(pier.2-1)
a= (pier.12 - pier.6 + pier.6 - pier.3)/ 2-1
a= (pier. 12-pier.3)/ 1

pier.12= pier.(4*3)=2pier.3
a=2pier.3 - pier.3
a= pier.3

b=0
y=pier.3 x
2 3 2